Composite pole piece, preparation method thereof and secondary battery

By coating the lithium-ion battery electrodes with a shape memory alloy coating, the gap between the electrodes can be dynamically adjusted, solving the thermal runaway problem of lithium-ion batteries under abnormal temperature rise and improving the battery's safety and thermal management performance.

CN121483986APending Publication Date: 2026-02-06SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511734298.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-24
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing lithium-ion battery electrodes have difficulty automatically adjusting their gaps when they experience abnormal temperature rises, leading to a high risk of thermal runaway and affecting battery safety and cycle stability.

Method used

An alloy coating method is used to coat the current collector surface with shape memory alloy (SMA). By utilizing its thermal response characteristics, the electrode gap is dynamically adjusted when the temperature changes, forming a three-dimensional heat dissipation channel and optimizing the heat transfer path inside the cell.

Benefits of technology

It significantly reduces the risk of thermal runaway, improves the thermal stability and safety of the battery, and enhances the battery's thermal management capabilities under complex operating conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121483986A_ABST
    Figure CN121483986A_ABST
Patent Text Reader

Abstract

The invention provides a composite pole piece, a preparation method thereof and a secondary battery. The composite pole piece comprises a current collector and a coating arranged on the surface of at least one side of the current collector, the coating is an alloy coating, and the preparation process of the composite pole piece comprises the following steps: sequentially smelting and cooling raw materials containing a nickel source, a titanium source, a molybdenum source, an aluminum source and a carbon source to obtain a first product; performing heat treatment on the first product to obtain a second product; carrying out atomization treatment on the second product to obtain a powdery third product; and coating at least one side surface of a current collector with the third product to form an alloy coating so as to obtain the composite pole piece. According to the invention, the functional shape memory alloy (SMA) is coated on the current collector as the thermal response coating, so that the purpose of adjusting the gap between the pole pieces in real time according to the temperature change is achieved, and the technical effects of optimizing the heat transfer path in the battery cell, reducing the risk of thermal runaway and improving the overall safety of the battery are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of secondary batteries, and in particular, to a composite electrode sheet, a preparation method thereof, and a secondary battery. BACKGROUND

[0002] The energy density and safety of lithium ion batteries are highly dependent on the stability of the electrode sheet structure. Generally, in a lithium ion battery, the internal structure of the battery cell mainly includes four parts: positive electrode, negative electrode, separator, and electrolyte. The electrode sheet is the main component of the positive electrode and the negative electrode. The electrode sheet is usually composed of active material, conductive agent, binder, and current collector. The active material layer is tightly attached to the metal current collector (such as copper foil or aluminum foil) through a coating process. This fixed electrode sheet structure can ensure good electrochemical performance during normal operation of the battery, but in abnormal situations such as overcharging, external short circuit, or high temperature environment, it is easy to cause thermal runaway, and even fire or explosion.

[0003] The traditional electrode sheet uses a fixed coating process (such as wet or dry coating), and the gap between the active material layer and the current collector is fixed by the initial process parameters. However, when the lithium battery is abnormally heated, the traditional fixed gap design increases the difficulty of heat dissipation during heat accumulation, which easily leads to irreversible thermal runaway.

[0004] Currently, in order to improve the safety of lithium batteries, the industry has taken various measures, including but not limited to improving the battery material system, optimizing the battery structure design, developing intelligent temperature control systems, etc. Among them, optimizing the internal structure design of the battery is an effective method, such as increasing the thickness of the separator, using high thermal stability electrolyte, and setting heat sinks inside the battery to enhance the thermal management capability of the battery. However, these methods either increase the volume and weight of the battery, affecting the energy density, or can only alleviate the problem to a certain extent, but not fundamentally solve the problem. In addition, in the prior art, the control of the electrode sheet gap mainly depends on the initial process parameters. Once the internal environment of the battery changes, such as temperature rise, the fixed electrode sheet gap cannot be self-adjusted, thereby affecting the heat conduction efficiency of the battery and increasing the risk of thermal runaway. In addition, the fixed design of the electrode sheet gap may suffer from stress damage due to the volume change of the active material during the battery cycle, further reducing the cycle stability and safety of the battery.

[0005] Generally, when the internal tab of the battery cell is locally overheated, the existing tab gap lacks a self-adjusting mechanism, which is easy to cause local overheating, leading to safety risks such as electrolyte decomposition and lithium dendrite growth, and increases the probability of thermal runaway. Therefore, how to provide a preparation method of a composite tab, so that the obtained tab can adjust the gap in real time according to the temperature change, thereby optimizing the heat transfer path inside the battery cell; at the same time, it can also disperse the local stress of the tab through the gap adjustment, to a certain extent, reduce the risk of interface side reaction at high temperature, and inhibit the occurrence of irreversible thermal runaway, is one of the important technical problems to be solved in the field. SUMMARY

[0006] The main purpose of the present application is to provide a composite tab, a preparation method thereof and a secondary battery, so as to solve the problem that the battery tab in the prior art is difficult to automatically adjust the tab gap when the battery abnormally heats, thereby causing poor battery safety and easy thermal runaway.

[0007] In order to achieve the above-mentioned purpose, the first aspect of the present application provides a preparation method of a composite tab, the composite tab comprising a current collector and a coating layer provided on at least one side surface of the current collector, the coating layer being an alloy coating layer, and the preparation process of the composite tab comprising: step S1, raw materials containing a nickel source, a titanium source, a molybdenum source, an aluminum source and a carbon source are sequentially subjected to melting and cooling treatment to obtain a first product; step S2, the first product is subjected to heat treatment to obtain a second product; step S3, the second product is subjected to atomization treatment to obtain a third product in powder form; step S4, the third product is coated on at least one side surface of the current collector to form an alloy coating layer, thereby obtaining a composite tab.

[0008] Further, the alloy coating layer comprises 60-90 parts by weight of Ni, 5-25 parts by weight of Ti, 0.1-2 parts by weight of Mo, 0.1-0.8 parts by weight of Al and 1-20 parts by weight of C.

[0009] Further, in step S1, the melting temperature of the melting is 800-1600℃; and / or, the melting is carried out under the condition that the vacuum degree is 10 -4 Pa-10 -3 Pa; and / or, the cooling rate of the cooling treatment is 80-100K / s.

[0010] Further, in step S2, the heat treatment is laser annealing treatment, and the power of the laser annealing treatment is 600-1000W, and the scanning speed is 0.5-2.0m / min; preferably, the power of the laser annealing treatment is 800±50W, and the scanning speed is 1.0±0.05m / min.

[0011] Further, in step S3, the atomization pressure of the atomization treatment is 1 MPa to 5 MPa, and the atomization temperature is 1000℃ to 1600℃; preferably, the atomization treatment is vacuum atomization, and the vacuum degree of the vacuum atomization is 1 Pa to 5 Pa.

[0012] Further, in step S4, the coating method is plasma spraying, the spraying pressure of the plasma spraying is 0.2 MPa to 0.8 MPa, preferably 0.5±0.05 MPa; and / or, the powder feeding rate of the plasma spraying is 30 g / min to 50 g / min; and / or, the arc power of the plasma spraying is 40 kW to 60 kW.

[0013] Further, the nickel source is high-purity nickel, and in the high-purity nickel, the mass fraction of nickel element is ≥99.9%; and / or, the titanium source is high-purity titanium, and in the high-purity titanium, the mass fraction of titanium element is ≥99.9%; and / or, the molybdenum source is nickel-molybdenum intermediate alloy, and in the nickel-molybdenum intermediate alloy, the mass fraction of molybdenum element is 5% to 10%; and / or, the aluminum source is nickel-aluminum intermediate alloy, and in the nickel-aluminum intermediate alloy, the mass fraction of aluminum element is 2% to 5%; and / or, the carbon source is carbon nanotube.

[0014] The second aspect of the present application provides a composite tab, which is prepared by the above-mentioned method for preparing a composite tab; the composite tab comprises a current collector and an alloy coating layer arranged on at least one side surface of the current collector.

[0015] Further, the thickness of the alloy coating layer is 6 μm to 20 μm, the phase transition temperature is 80℃ to 120℃, and the porosity is 5% to 25%; and / or, the current collector is a positive electrode current collector or a negative electrode current collector, and the positive electrode current collector is an aluminum foil, and the negative electrode current collector is a copper foil and / or a nickel foil.

[0016] A secondary battery comprising the above-mentioned composite tab.

[0017] By applying the technical scheme of the present application, the functional shape memory alloy (SMA) is arranged on the current collector as a thermal response coating layer, so as to achieve the purpose of adjusting the tab gap in real time according to temperature change, thereby realizing the technical effects of optimizing the heat transfer path inside the battery cell, reducing the risk of thermal runaway, and improving the overall safety of the battery. When the battery abnormally heats up, the SMA coating layer changes phase and expands under heat, so as to increase the tab gap, build a three-dimensional heat dissipation channel, significantly reduce the internal thermal resistance of the battery cell, effectively disperse heat, inhibit the interface side reaction caused by local overheating, reduce the probability of thermal runaway, and enhance the thermal stability of the battery under complex working conditions. BRIEF DESCRIPTION OF DRAWINGS

[0018] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate an implementation of the application and, together with the description, serve to explain the application. In the drawings,

[0019] Figure 1 Scanning electron microscope (SEM) characterization results of the third product obtained in Example 1 of the present application. DETAILED DESCRIPTION

[0020] It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other without conflict. The present application will be described in detail below with reference to the embodiments.

[0021] As described in the background, the prior art battery pole piece is difficult to automatically adjust the pole piece gap when the battery abnormally heats, thereby causing the battery to have the problems of poor safety and easy thermal runaway. In order to solve the above technical problems, the first aspect of the present application provides a preparation method of a composite pole piece, the composite pole piece comprising a current collector and a coating layer provided on at least one side surface of the current collector, the coating layer being an alloy coating layer, and the preparation process of the composite pole piece comprising: step S1, raw materials containing a nickel source, a titanium source, a molybdenum source, an aluminum source and a carbon source are sequentially subjected to melting and cooling treatment to obtain a first product; step S2, the first product is subjected to heat treatment to obtain a second product; step S3, the second product is subjected to atomization treatment to obtain a third product in the form of powder; and step S4, the third product is coated on at least one side surface of the current collector to form an alloy coating layer, thereby obtaining the composite pole piece.

[0022] The present application utilizes the synergistic effect of Ni, Ti, molybdenum Mo, aluminum Al and carbon C, and forms an alloy coating layer with thermal response characteristics through the process flow of melting, heat treatment, atomization and coating. The coating layer can dynamically adjust the pole piece gap when the internal temperature of the lithium battery changes, and improve the thermal management performance of the battery. In the above preparation method, specifically: in step S1, the nickel source and the titanium source in the raw materials are the basis for forming a shape memory alloy, and the introduction of the molybdenum source, the aluminum source and the carbon source is to further optimize the phase transition temperature and thermal expansion performance of the SMA, and to improve its stability and response speed in a high temperature environment. The uniform mixing of alloy elements is achieved by melting, which lays a good foundation for subsequent heat treatment. The heat treatment in step S2 can promote the sufficient diffusion between the alloy elements, refine the grains, and ensure that the material exhibits good phase transition characteristics in a specific temperature range, thereby improving its thermal response performance. The atomization treatment in step S3 is used to convert the alloy material after heat treatment into uniform and fine powder, thereby optimizing the uniformity and density of the coating obtained in the subsequent coating. Finally, the SMA composite material in the form of powder is uniformly coated on the surface of the current collector in step S4.

[0023] In summary, in the obtained alloy coating, nickel and titanium are the basic components of the shape memory alloy, the addition of molybdenum increases the phase transition temperature, making it more suitable for the normal working temperature range of the secondary battery. The addition of aluminum refines the grain and improves the high-temperature stability of the coating, and the small amount of carbon incorporated improves the thermal expansion capacity. The synergistic effect of these elements, combined with the above-mentioned specific preparation process, enables the coating to respond quickly when facing abnormal temperature rise of the battery, and through the expansion force generated by phase transition, it automatically adjusts the gap between the pole pieces to form an effective heat dissipation channel, significantly reducing the risk of thermal runaway, optimizing the thermal management performance of the battery, and at the same time enhancing the cycle stability and safety of the battery.

[0024] In several preferred embodiments, the alloy coating includes 60-90 parts by weight of Ni, 5-25 parts by weight of Ti, 0.1-2 parts by weight of Mo, 0.1-0.8 parts by weight of Al, and 1-20 parts by weight of C. Within this preferred component content range, the performance of the resulting composite SMA coating is further optimized, exhibiting higher phase transition temperature stability, better thermal expansion response, and stronger fatigue resistance, thereby maintaining higher thermal management and mechanical stability during battery cycling and more effectively extending the service life of the secondary battery in which it is used.

[0025] In several more preferred embodiments, the alloy coating includes 70-80 parts by weight of Ni, 10-20 parts by weight of Ti, 0.2-0.8 parts by weight of Mo, 0.2-0.3 parts by weight of Al, and 1-15 parts by weight of C. By further optimizing the ratio of each component as above, the thermal response characteristics of the SMA coating can be further optimized without sacrificing the energy density of the battery. Among them, the appropriate amount of Ni and Ti enhances the strength of the shape memory effect, and the appropriate addition of Mo and Al enhances the phase transition temperature and the stability of the coating, respectively, and the presence of C further enhances the thermal expansion capacity of the obtained alloy coating. The synergistic effect of each component within the above preferred range enables the composite pole piece to more effectively manage heat under abnormal battery conditions, thereby further ensuring the operational safety of the battery.

[0026] Further, in the alloy coating, the ratio of the total weight of Ni and Ti to the weight of Mo is preferably (120-240): 1, so as to more significantly exert the thermal stability of Mo, so that the obtained alloy coating can more quickly undergo phase transition when the temperature inside the battery rises, forming three-dimensional heat dissipation channels, more effectively dispersing heat, thereby more effectively reducing the possibility of local overheating triggering thermal runaway. In addition, the addition of Al helps to refine the grain structure of the SMA coating and improve its stability at high temperatures, while also helping to improve the thermal expansion performance of the coating. Therefore, the ratio of the total weight of Ni and Ti to the weight of Al is preferably (120-450): 1, so as to facilitate the obtained alloy coating not only to effectively respond to temperature changes, but also to better maintain structural stability in long-term cycling, reduce the decline in battery performance due to coating aging or failure, and thereby more significantly enhance the overall safety and reliability of the battery.

[0027] In the preparation process of the above-mentioned first product, in order to facilitate the alloying elements to be more fully dissolved and mixed, and at the same time promote the alloying of the Ni-Ti based shape memory alloy with Mo, Al and C, forming a more uniform alloy melt, the smelting temperature of smelting is preferably 800-1600°C, and the finally obtained alloy coating has more significant thermal response, and more significantly improves the thermal stability and safety of the obtained composite tab. Preferably, smelting is carried out under the condition that the vacuum degree is 10 -4 Pa~10 -3 Pa, so as to more effectively remove oxygen and other impurities in the melt, reduce the formation of oxides, and thereby more significantly optimize the phase transition characteristics and thermal expansion performance of the obtained alloy coating. During the cooling process, the cooling rate of the cooling process is preferably 80-100 K / s, so as to further promote the ordered arrangement of alloying elements, which is conducive to the formation of more stable metallographic structure, and also further promotes grain refinement and more uniform phase distribution, and finally more effectively improves the mechanical properties and thermal response sensitivity of the obtained alloy coating and the obtained composite tab.

[0028] In step S2, the heat treatment is preferably a laser annealing treatment. Compared with other heat treatment methods, laser annealing is a heat treatment method in a non-equilibrium state, which can accurately control the temperature of the material surface in a short time, help to refine the microstructure of the material, and improve the density and uniformity of the material surface. On this basis, for the alloy element system provided in the present application, the power of the laser annealing treatment is preferably 600W-1000W (preferably 800±50W), and the scanning speed is 0.5m / min-2.0m / min (preferably 1.0±0.05m / min), thereby effectively promoting the rearrangement of alloy elements and forming a shape memory alloy coating with high thermal expansion coefficient and wider phase transition temperature range in the subsequent process, so that it can respond more quickly and effectively when the temperature in the battery changes, realize dynamic adjustment of the inter-electrode gap, and ultimately more significantly optimize the thermal management of the battery.

[0029] In step S3, the molten alloy is converted into fine powder by atomization treatment. The atomization pressure of the atomization treatment is preferably 1MPa-5MPa, and the atomization temperature is 1000℃-1600℃, which can promote the alloy to break into fine droplets quickly, form powder particles with higher sphericity, smaller surface energy and better flowability, thereby forming a more uniform, denser and more stable coating in subsequent coating, further strengthening the thermal management function of the obtained composite electrode. In several typical embodiments, the atomization treatment is vacuum atomization, and the vacuum degree of the vacuum atomization is 1Pa-5Pa. The powder formed under this preferred condition has higher density and lower porosity, which means that the alloy coating formed after coating has better mechanical properties and thermal conductivity, and can respond more effectively to changes in the temperature in the battery. And more preferably, the D50 of the third product is 20μm-50μm, so as to form a more continuous and dense alloy coating in subsequent coating, and also promote the phase transition characteristics and thermal expansion capacity of the obtained alloy coating to be more stable, thereby better realizing the dynamic adjustment function of the inter-electrode gap of the obtained composite electrode.

[0030] In step S4, the preferred coating method is plasma spraying. Compared with other coating methods, the high temperature in the plasma spraying process can cause the powder to melt instantaneously and solidify rapidly, forming a tightly bonded coating layer, while optimizing the grain boundary, phase distribution and porosity of the formed alloy coating layer, and improving the dynamic adjustment effect of the gap. More preferably, the spraying pressure of the plasma spraying is 0.2 MPa to 0.8 MPa, more preferably 0.5 ± 0.05 MPa; and / or, the powder feeding rate of the plasma spraying is 30 g / min to 50 g / min; and / or, the arc power of the plasma spraying is 40 kW to 60 kW. In the above-mentioned plasma spraying process, by gradually optimizing the spraying pressure, the powder can be made to impact the current collector surface at a more appropriate speed, forming a more robust coating layer; at the same time, it can also more effectively reduce the rebound of the powder during the spraying process, reducing the loss. By gradually optimizing the powder feeding rate, a more appropriate thickness of the alloy coating layer can be obtained, so as to provide sufficient thermal expansion capability without excessively increasing the internal space occupation of the battery, thereby better maintaining the energy density of the corresponding battery. By gradually optimizing the arc power, the melting and solidification process of the coating layer can be better balanced, forming a more uniform and dense microstructure, and the bonding strength of the coating layer and the current collector can be further improved, which can more effectively withstand the mechanical stress during the battery cycle process. In abnormal working conditions, such as a sharp rise in the internal temperature of the battery, the alloy coating layer prepared by the above-mentioned preferred process can respond more quickly and more effectively through phase transition to generate expansion force, adjust the inter-tab gap, form an effective heat dissipation channel, and ultimately more significantly improve the overall safety and reliability of the obtained composite tab and the battery.

[0031] In several typical embodiments, in order to obtain an alloy coating layer with higher purity and better performance, thereby more significantly improving the thermal management capability of the obtained composite tab, it is preferred that: the nickel source is high-purity nickel, and in the high-purity nickel, the mass fraction of nickel element is ≥ 99.9%; and / or, the titanium source is high-purity titanium, and in the high-purity titanium, the mass fraction of titanium element is ≥ 99.9%; and / or, the molybdenum source is nickel-molybdenum intermediate alloy, and in the nickel-molybdenum intermediate alloy, the mass fraction of molybdenum element is 5% to 10%; and / or, the aluminum source is nickel-aluminum intermediate alloy, and in the nickel-aluminum intermediate alloy, the mass fraction of aluminum element is 2% to 5%; and / or, the carbon source is carbon nanotube. Because the unique structure of the carbon nanotube can form a "skeleton" inside the material after being incorporated into the SMA coating layer, thereby further improving the thermal expansion capability of the obtained alloy coating layer, therefore, for the carbon nanotube used, it is preferred that its diameter is 5 nm to 10 nm, and the aspect ratio is 100 to 150.

[0032] The second aspect of the present application provides a composite electrode tab, which is prepared by the above-mentioned method for preparing a composite electrode tab; the composite electrode tab comprises a current collector and an alloy coating arranged on at least one side surface of the current collector. Due to the above-mentioned alloy coating prepared by the present application and provided with a special dynamic gap adjustment mechanism, the internal thermal resistance of the battery in which the composite electrode tab is arranged can be effectively reduced, and the heat can be more uniformly distributed, thereby reducing the probability of thermal runaway.

[0033] It should be particularly pointed out that, due to the formation of complex structures and changes in composition during the preparation process, and due to the limitations of the special nature of the material field and the existing test characterization means, it is difficult to comprehensively and quantitatively characterize the microstructure of the above-mentioned composite electrode tab, especially the alloy coating therein. However, the performance test results show that the above-mentioned composite electrode tab obtained by the present application has more stable performance when used in a battery system, and is less likely to occur thermal runaway in application.

[0034] In several preferred embodiments, the thickness of the alloy coating is preferably 6 μm to 20 μm, the phase transition temperature is 80℃ to 120℃, and the porosity is 5% to 25%, so that the obtained composite electrode tab can play a more stable role in the normal and abnormal temperature range of the battery, especially in the initial stage of thermal runaway, it can respond more timely, disperse heat by adjusting the electrode tab gap, reduce its severe accumulation, thereby more effectively improving the thermal management capability of the secondary battery. In addition, the current collector is a positive electrode current collector or a negative electrode current collector, and the positive electrode current collector is an aluminum foil, and the negative electrode current collector is a copper foil and / or a nickel foil.

[0035] A secondary battery comprising the above-mentioned composite electrode tab. Relying on the dynamic gap adjustment mechanism of the alloy coating in the above-mentioned composite electrode tab provided by the present application, the corresponding secondary battery has better safety. When the internal temperature of the battery abnormally rises, the coating undergoes phase transition and volume expansion, automatically adjusts the electrode tab gap, and creates a heat dissipation channel. This mechanism can quickly reduce the internal thermal resistance of the battery, so that the heat is more uniformly distributed in the battery, reducing the local high temperature phenomenon, effectively inhibiting the spread of thermal runaway, and significantly improving the safety and reliability of the battery.

[0036] The present application will be further described in detail below in conjunction with specific examples, which cannot be understood as limiting the scope of the present application.

[0037] Unless otherwise defined, all professional terms used herein have the same meaning as generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the protection scope of the present application.

[0038] Example 1

[0039] A preparation method of a composite electrode tab, the composite electrode tab being a positive electrode tab:

[0040] (1-1) Ingredients: high-purity nickel ingots (purity ≥ 99.9wt.%) and titanium ingots (purity ≥ 99.9wt.%) are selected, and the mass ratio is 10:3; nickel-molybdenum intermediate alloy (Mo content 8wt.%) is added to increase the phase transition temperature by solid solution strengthening; nickel-aluminum intermediate alloy (Al content 3wt.%) is added to refine the grain and enhance the high-temperature stability; carbon nanotubes (diameter 8nm, aspect ratio 120) are added to form carbide precipitates by carburizing treatment to improve the thermal expansion capacity, and a mixed raw material is obtained.

[0041] (1-2) The above raw materials are collectively subjected to induction melting in a vacuum environment, the temperature is controlled to be 1500℃, the vacuum degree is 10 -3 Pa, and the uniform distribution of alloy components is ensured to obtain a melt. The obtained melt is cooled at a cooling rate of 100K / S to obtain a first product.

[0042] (2) The above first product is subjected to laser annealing, the power is controlled to be 800W, and the scanning speed is controlled to be 1m / min to improve the surface density, and a second product is obtained.

[0043] (3) The above annealed alloy material is subjected to vacuum atomization (vacuum degree 5Pa), the pressure is controlled to be 3MPa, and the temperature is controlled to be 1200℃ to ensure the uniformity and sphericity of the atomized powder, and a third product with D50=30μm is obtained.

[0044] The SEM characterization results of the obtained third product are shown in Figure 1 .

[0045] (4) Aluminum foil is selected as the positive electrode current collector, and the spraying pressure of plasma spraying is set to 0.5MPa, the powder feeding rate is 30g / min, and the arc power is 40kW. The obtained powder is subjected to plasma spraying, and an alloy coating with a thickness of 15μm is formed on one side surface of the positive electrode current collector, and a composite electrode tab is obtained.

[0046] In the obtained alloy coating, 80% of Ni, 18% of Ti, 0.7% of Mo, 0.3% of Al, and 1% of C are contained, i.e. (Ni+Ti) / Mo=136, (Ni+Ti) / Al=127.

[0047] Example 2

[0048] A preparation method of a composite electrode tab, the composite electrode tab being a negative electrode tab:

[0049] (1-1) Preparation of raw materials: high purity nickel ingot (purity≥99.9wt.%) and titanium ingot (purity≥99.9wt.%) are selected, and the mass ratio is 5:1; nickel-molybdenum intermediate alloy (Mo content 5wt.%) is added to increase the phase transition temperature by solid solution strengthening; nickel-aluminum intermediate alloy (Al content 3wt.%) is added to refine the grain and enhance the high-temperature stability; carbon nanotubes (diameter 8nm, aspect ratio 120) are added to form carbide precipitates by carburizing treatment to improve the thermal expansion capacity, and the mixed raw materials are obtained.

[0050] (1-2) The above raw materials are collectively subjected to induction melting in a vacuum environment, the temperature is controlled to 1500℃, the vacuum degree is 10 -3 Pa, and the uniform distribution of alloy components is ensured to obtain a melt. The obtained melt is cooled at a cooling rate of 80K / s to obtain a first product.

[0051] (2) Laser annealing is adopted for the above first product, the power is controlled to 800W, and the scanning speed is controlled to 1m / min to improve the surface density, and a second product is obtained.

[0052] (3) The annealed alloy material is subjected to vacuum atomization (vacuum degree 5Pa), the pressure is controlled to 3MPa, and the temperature is controlled to 1200℃ to ensure the uniformity and sphericity of the atomized powder, and a third product with D50=25μm is obtained.

[0053] (4) Copper foil is selected as the negative current collector, and the spraying pressure of plasma spraying is set to 0.8MPa, the powder feeding rate is 50g / min, and the arc power is 60kW. The obtained powder is subjected to plasma spraying, and an alloy coating with a thickness of 18μm is formed on the surface of the negative current collector, and a composite electrode plate is obtained.

[0054] In the obtained alloy coating, 72% of Ni, 12% of Ti, 0.4% of Mo, 0.2% of Al and 14% of C are contained, i.e. (Ni+Ti) / Mo=212.5, (Ni+Ti) / Al=425.

[0055] Example 3

[0056] A preparation method of a composite electrode plate, the composite electrode plate being a positive electrode plate:

[0057] The difference between this embodiment and Example 1 is only that the melting temperature in step (1) is changed to 700℃.

[0058] Example 4

[0059] A preparation method of a composite electrode plate, the composite electrode plate being a positive electrode plate:

[0060] The difference between this example and Example 1 is that the temperature of the melting in step (1) is changed to 1800°C.

[0061] Example 5

[0062] A method for producing a composite electrode sheet, the composite electrode sheet being a positive electrode sheet:

[0063] The difference between this example and Example 1 is that the cooling rate of the melt after the melting in step (1) is changed to 50 K / s.

[0064] Example 6

[0065] A method for producing a composite electrode sheet, the composite electrode sheet being a positive electrode sheet:

[0066] The difference between this example and Example 1 is that the cooling rate of the melt after the melting in step (1) is changed to 150 K / s.

[0067] Example 7

[0068] A method for producing a composite electrode sheet, the composite electrode sheet being a positive electrode sheet:

[0069] The difference between this example and Example 1 is that the power of the laser annealing in step (2) is changed to 600 W and the scanning speed is changed to 0.5 m / min.

[0070] Example 8

[0071] A method for producing a composite electrode sheet, the composite electrode sheet being a positive electrode sheet:

[0072] The difference between this example and Example 1 is that the power of the laser annealing in step (2) is changed to 1000 W and the scanning speed is changed to 2.0 m / min.

[0073] Example 9

[0074] A method for producing a composite electrode sheet, the composite electrode sheet being a positive electrode sheet:

[0075] The difference between this example and Example 1 is that the pressure of the atomization treatment in step (3) is changed to 0.5 MPa and the temperature is changed to 1800°C, and further the third product having a D50 of 15 μm is obtained.

[0076] Example 10

[0077] A method for producing a composite electrode sheet, the composite electrode sheet being a positive electrode sheet:

[0078] The difference between this example and Example 1 is that the pressure of the atomization treatment in step (3) is changed to 6.0 MPa and the temperature is changed to 800°C, and further the third product having a D50 of 55 μm is obtained.

[0079] Example 11

[0080] A method for preparing a composite electrode tab, the composite electrode tab being a positive electrode tab:

[0081] The difference between this example and Example 1 is that in step (4), the spraying pressure of the plasma spraying is changed to 0.1 MPa, the powder feeding rate is changed to 20 g / min, and the arc power is changed to 30 kW.

[0082] Example 12

[0083] A method for preparing a composite electrode tab, the composite electrode tab being a positive electrode tab:

[0084] The difference between this example and Example 1 is that in step (4), the spraying pressure of the plasma spraying is changed to 1.0 MPa, the powder feeding rate is changed to 60 g / min, and the arc power is changed to 70 kW.

[0085] Example 13

[0086] A method for preparing a composite electrode tab, the composite electrode tab being a positive electrode tab:

[0087] The difference between this example and Example 1 is that the addition amount of each raw material is changed to obtain an alloy coating with different ingredient contents. Specifically: in the obtained alloy coating, 60% of Ni, 20% of Ti, 0.2% of Mo, 0.8% of Al, and 19% of C are contained, i.e. (Ni+Ti) / Mo=400, (Ni+Ti) / Al=100.

[0088] Example 14

[0089] A method for preparing a composite electrode tab, the composite electrode tab being a positive electrode tab:

[0090] The difference between this example and Example 1 is that the addition amount of each raw material is changed to obtain an alloy coating with different ingredient contents. Specifically: in the obtained alloy coating, 90% of Ni, 5% of Ti, 2% of Mo, 0.1% of Al, and 2.9% of C are contained, i.e. (Ni+Ti) / Mo=47.5, (Ni+Ti) / Al=950.

[0091] Example 15

[0092] A method for preparing a composite electrode tab, the composite electrode tab being a positive electrode tab:

[0093] The difference between this example and Example 1 is that in step (2), laser annealing is not used, but the first product is placed in a tube furnace and subjected to ordinary annealing heat treatment under an argon atmosphere at a holding temperature of 400°C for a holding time of 3 h.

[0094] Example 16

[0095] A method for preparing a composite electrode tab, the composite electrode tab being a positive electrode tab:

[0096] This example differs from Example 1 only in that step (5) is not performed, i.e. plasma spraying is not performed, but the atomized third particles in powder form are dispersed in ethanol and directly coated and dried to obtain an alloy coating layer with a thickness of 50 μm, thereby obtaining a composite electrode tab sample.

[0097] Comparative Example 1

[0098] A method for preparing a composite electrode tab, the composite electrode tab being a positive electrode tab:

[0099] This comparative example differs from Example 1 only in that the nickel-molybdenum intermediate alloy is not added.

[0100] Comparative Example 2

[0101] A method for preparing a composite electrode tab, the composite electrode tab being a positive electrode tab:

[0102] This comparative example differs from Example 1 only in that the nickel-aluminum intermediate alloy is not added.

[0103] Comparative Example 3

[0104] A method for preparing a composite electrode tab, the composite electrode tab being a positive electrode tab:

[0105] This comparative example differs from Example 1 only in that the carbon nanotubes are not added.

[0106] Comparative Example 4

[0107] A method for preparing a composite electrode tab, the composite electrode tab being a positive electrode tab:

[0108] This comparative example differs from Example 1 only in that step (2) is not performed, i.e. heat treatment is not performed, but the first product obtained by smelting is directly atomized and the subsequent steps are performed.

[0109] Porosity of the alloy coating layer on the composite electrode tab: obtained according to the mercury intrusion method.

[0110] Phase transition temperature of the alloy coating layer on the composite electrode tab: obtained according to the differential scanning calorimetry method.

[0111] Battery sample preparation and testing method

[0112] For the case where the sample is a positive electrode tab: the composite positive electrode tab samples obtained in each example and comparative example are used as positive electrode tabs, graphite is used as negative electrode, ethylene carbonate + diethyl carbonate (volume ratio 1:1) + 1M lithium hexafluorophosphate is used as electrolyte, and a battery sample with a capacity of 3 Ah is assembled.

[0113] For the case that the sample is a negative electrode sheet: the composite negative electrode sheet samples obtained in each of the examples and the comparative examples are taken as negative electrode sheets, lithium iron phosphate is taken as a positive electrode, ethylene carbonate + diethyl carbonate (volume ratio 1:1) + 1M lithium hexafluorophosphate is taken as an electrolyte, and each battery sample with a capacity of 3.5 Ah is assembled.

[0114] Subsequently, the thermal stability performance test is performed on each of the battery samples under the condition of a temperature box at 160°C, and the thermal runaway time is obtained. In this process, when the surface temperature rise rate of the battery is ≥1°C / s, or a fire or even an explosion phenomenon has occurred, it is determined that the battery sample has undergone thermal runaway.

[0115] The results obtained in the above test are shown in Table 1.

[0116] Table 1

[0117]

[0118] From the above description, it can be seen that the above-mentioned embodiments of the present application realize the preparation of a composite electrode sheet with superior performance by coating a functionalized shape memory alloy (SMA) on the current collector as a thermal response coating. The alloy coating in the obtained composite electrode sheet has a special dynamic gap adjustment mechanism, and relying on this mechanism, the purpose of adjusting the electrode sheet gap in real time according to temperature changes is ultimately achieved, thereby realizing the technical effects of optimizing the heat transfer path inside the battery cell, reducing the risk of thermal runaway, and improving the overall safety of the battery.

[0119] In each of the embodiments:

[0120] Comparing Example 3 and Example 4 with Example 1, it can be seen that by optimizing the temperature of smelting, the alloying elements can be more fully dissolved and mixed, and at the same time, the alloying of the Ni-Ti-based shape memory alloy with Mo, Al and C is promoted, forming a more uniform alloy melt, and ultimately obtaining an alloy coating with more significant thermal response, which more significantly improves the thermal stability and safety of the obtained composite electrode sheet.

[0121] Comparing Example 5 and Example 6 with Example 1, it can be seen that by optimizing the cooling rate after the smelting stage, the ordered arrangement of alloying elements is further promoted, which is beneficial to form a more stable metallographic structure, and at the same time, further promotes grain refinement, and the phase distribution is more uniform, ultimately more effectively improving the mechanical properties and thermal response sensitivity of the obtained alloy coating and the obtained composite electrode sheet.

[0122] Comparing Example 7, 8 and 15 with Example 1, it can be seen that by preferably annealing in the form of laser annealing, and further preferably the power and scanning speed of the laser annealing used, the temperature of the material surface can be accurately controlled in a short time, which helps to refine the microstructure of the material, and improve the density and uniformity of the material surface. In addition, it can more effectively promote the rearrangement of alloying elements and form a shape memory alloy coating with high thermal expansion coefficient and wider phase transition temperature range in the subsequent process, so that it can respond more quickly and effectively when the temperature inside the battery changes, and realize dynamic adjustment of the interstitial gap of the electrode, and finally more significantly optimize the thermal management inside the battery.

[0123] Comparing Example 9, 10 with Example 1, it can be seen that by preferably selecting the conditions of atomization treatment, and further preferably the median particle size D50 of the obtained third product, the alloy can be quickly broken into small droplets, forming powder particles with higher sphericity, smaller surface energy and better flowability, thereby forming a more uniform, denser and more stable coating in the subsequent coating process. At the same time, it also promotes the stability of the phase transition characteristics and thermal expansion capacity of the obtained alloy coating, thereby better realizing the dynamic adjustment function of the interstitial gap of the obtained composite electrode.

[0124] Comparing Example 11, 12 with Example 1, it can be seen that by preferably selecting the condition parameters of plasma spraying, the powder can be made to impact the current collector surface at a more appropriate speed to form a more robust coating; at the same time, it also more effectively reduces the rebound of the powder during the spraying process, reducing waste. By gradually selecting the powder feeding rate to obtain an alloy coating with a more appropriate thickness, the internal space occupation of the battery can be further reduced while providing sufficient thermal expansion capacity, thereby better maintaining the energy density of the corresponding battery. At the same time, a more uniform and dense microstructure can be formed, and the bonding strength of the coating and the current collector can be further improved, more effectively resisting mechanical stress during battery cycling.

[0125] Comparing Example 13, 14 with Example 1, it can be seen that by preferably selecting the component content of the alloy coating, the thermal response characteristics of the SMA coating can be further optimized without sacrificing the energy density of the battery. The synergistic effect of the components within the above preferred range enables the composite electrode to more effectively manage heat under abnormal battery operating conditions, thereby further ensuring the safety of the battery in operation.

[0126] And through Example 16, it can be seen that compared with other coating methods, the high temperature in the plasma spraying process can cause the powder to melt instantaneously and solidify rapidly, forming a tightly bonded coating, while optimizing the grain boundary, phase distribution and porosity of the formed alloy coating, and improving its dynamic adjustment effect of the interstitial gap.

[0127] It should be noted that the terms "first", "second", and the like in the description and in the claims of the present application are used for distinguishing between similar objects and not necessarily for describing a particular sequential or chronological order. It is to be understood that the terms so used are interchangeable under appropriate circumstances such that the embodiments of the present application described herein are, for example, capable of orderly execution or performance.

[0128] The preferred embodiments of the application are described above in detail. The application is not limited to the embodiments described above, but can vary and be modified in various ways. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the application should be included in the scope of the protection of the application.

Claims

1. A method for preparing a composite electrode, the composite electrode comprising a current collector and a coating disposed on at least one surface of the current collector, characterized in that, The coating is an alloy coating, and the preparation process of the composite electrode includes: Step S1 involves sequentially smelting and cooling raw materials containing nickel, titanium, molybdenum, aluminum, and carbon sources to obtain the first product. Step S2: The first product is heat-treated to obtain the second product; Step S3: The second product is atomized to obtain a powdered third product; Step S4: The third product is coated onto at least one side surface of the current collector to form the alloy coating, thereby obtaining the composite electrode.

2. The method for preparing the composite electrode according to claim 1, characterized in that, The alloy coating comprises, by weight, 60-90 parts Ni, 5-25 parts Ti, 0.1-2 parts Mo, 0.1-0.8 parts Al, and 1-20 parts C.

3. The method for preparing the composite electrode according to claim 1 or 2, characterized in that, In step S1 The melting temperature is 800℃~1600℃; and / or, The melting is carried out under a vacuum of 10. -4 ~10 -3 Performed under the conditions of Pa; and / or, The cooling rate of the cooling process is 80K / s to 100K / s.

4. The method for preparing the composite electrode according to any one of claims 1 to 3, characterized in that, In step S2, the heat treatment is laser annealing, and the power of the laser annealing is 600W~1000W, and the scanning speed is 0.5m / min~2.0m / min; Preferably, the power of the laser annealing process is 800±50W and the scanning speed is 1.0±0.05m / min.

5. The method for preparing the composite electrode according to any one of claims 1 to 4, characterized in that, In step S3, the atomization pressure of the atomization treatment is 1MPa~5MPa, and the atomization temperature is 1000℃~1600℃. Preferably, the atomization process is vacuum atomization, and the vacuum degree of the vacuum atomization is 1 Pa to 5 Pa.

6. The method for preparing the composite electrode according to any one of claims 1 to 5, characterized in that, In step S4, the coating method is plasma spraying; The plasma spraying pressure is 0.2 MPa to 0.8 MPa; and / or, The powder feeding rate for plasma spraying is 30 g / min to 50 g / min; and / or, The arc power of the plasma spraying is 40kW~60kW.

7. The method for preparing the composite electrode according to any one of claims 1 to 6, characterized in that, The nickel source is high-purity nickel, and the mass fraction of nickel in the high-purity nickel is ≥99.9%; and / or, The titanium source is high-purity titanium, and the mass fraction of titanium in the high-purity titanium is ≥99.9%; and / or, The molybdenum source is a nickel-molybdenum master alloy, and the mass fraction of molybdenum in the nickel-molybdenum master alloy is 5%~10%; and / or, The aluminum source is a nickel-aluminum master alloy, and the mass fraction of aluminum in the nickel-aluminum master alloy is 2%~5%; and / or, The carbon source is carbon nanotubes.

8. A composite electrode, characterized in that, The composite electrode is prepared by the method for preparing a composite electrode according to any one of claims 1 to 7; the composite electrode includes the current collector and the alloy coating disposed on at least one side surface of the current collector.

9. The composite electrode according to claim 8, characterized in that, The alloy coating has a thickness of 6μm to 20μm, a phase transformation temperature of 80℃ to 120℃, and a porosity of 5% to 25%; and / or, The current collector is either a positive current collector or a negative current collector, wherein the positive current collector is aluminum foil and the negative current collector is copper foil and / or nickel foil.

10. A secondary battery, characterized in that, The secondary battery includes the composite electrode as described in claim 8 or 9.